2018
DOI: 10.1096/fj.201701315r
|View full text |Cite|
|
Sign up to set email alerts
|

Uncoupling effects of estrogen receptor α on LKB1/AMPK interaction upon adiponectin exposure in breast cancer

Abstract: Adipose tissue is a metabolic and endocrine organ that secretes bioactive molecules called adipocytokines. Among these, adiponectin has a crucial role in obesity-associated breast cancer. The key molecule of adiponectin signaling is AMPK, which is mainly activated by liver kinase B1 (LKB1). Here, we demonstrated that estrogen receptor-α (ERα)/LKB1 interaction may negatively interfere with the LKB1 capability to phosphorylate AMPK and inhibit its downstream signaling TSC2/mTOR/p70S6k. In adiponectin-treated MCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 62 publications
5
79
0
Order By: Relevance
“…Moreover, pretreatment of MDA‐MB‐231 breast cancer cells with adiponectin or its intra‐tumoural or systemic administration reduced mammary tumour growth in xenograft models, through the involvement of PI3K/Akt/and GSK‐β‐catenin signalling . In agreement with these findings, our recent data demonstrated a marked reduction of tumour size in adiponectin‐pretreated MDA‐MB‐231 cells implanted in nude mice, as also evidenced by a decreased expression of tumour cell mitotic index Ki67, concomitant with an enhanced activation of AMPK signalling . Besides, in another murine mammary tumour model, administration of adiponectin into tumour mass stimulated PP2A activity through AMPK, inhibiting cell growth and invasiveness .…”
Section: Adiponectin and Breast Cancer Growth And Progression: A Contsupporting
confidence: 84%
See 4 more Smart Citations
“…Moreover, pretreatment of MDA‐MB‐231 breast cancer cells with adiponectin or its intra‐tumoural or systemic administration reduced mammary tumour growth in xenograft models, through the involvement of PI3K/Akt/and GSK‐β‐catenin signalling . In agreement with these findings, our recent data demonstrated a marked reduction of tumour size in adiponectin‐pretreated MDA‐MB‐231 cells implanted in nude mice, as also evidenced by a decreased expression of tumour cell mitotic index Ki67, concomitant with an enhanced activation of AMPK signalling . Besides, in another murine mammary tumour model, administration of adiponectin into tumour mass stimulated PP2A activity through AMPK, inhibiting cell growth and invasiveness .…”
Section: Adiponectin and Breast Cancer Growth And Progression: A Contsupporting
confidence: 84%
“…Indeed, immunofluorescence analysis and proximity ligation assay, in cells treated with adiponectin, revealed that LKB1 localized in both nucleus and cytoplasm in MCF‐7 cells, while in MDA‐MB‐231 cells, it was mostly detectable in the cytoplasm. The nuclear localization of LKB1/ERα highlights the well‐documented role of LKB1 as ERα coactivator (Figure B). These findings were further supported by the observation that adiponectin exposure induced the recruitment of LKB1 on a classic ER element sequence located in the promoter region of estrogen‐dependent genes .…”
Section: Evidences Of the Interfering Role Of Erα In The Adiponectin/mentioning
confidence: 73%
See 3 more Smart Citations